(untitled) (Asian Journal of Social Science Studies, 2022)
The cultivation of Business English talents is of great significance to Chinese people‟s promotion of international cooperation and economic growth. However, the colleges and universities in China are still exploring how to best achieve this goal. By interviewing four Business English graduates who are currently working in the sector of international trade, this study attempts to investigate the gap between the curriculum design and the actual ability requirement for Business English majors. The analysis shows that gaps exist in all the six aspects, namely comprehensive quality, theoretical knowledge, practical experience, industry knowledge and general knowledge. The lack of practical experience and industry knowledge are most prominent. This study reveals that there is room for improvement in the current training programs for Business English, especially the modules of parallel classroom, theoretical courses, practical teaching, cooperation between schools and enterprises and general courses.